2008
DOI: 10.1021/je800188a
|View full text |Cite
|
Sign up to set email alerts
|

Re-Evaluation of the Thermodynamic Activity Quantities in Aqueous Sodium and Potassium Chloride Solutions at 25 °C

Abstract: The Hu ¨ckel equation is used to correlate the experimental activities of dilute NaCl and KCl solutions up to a molality of about 1.0 mol • kg -1 . The two parameters of this equation are dependent on the electrolyte and are B [which is simply related to the ion-size parameter (a*) in the Debye-Hu ¨ckel equation] and b 1 (which is the coefficient of the linear term in molality and related to hydration numbers of the ions of the electrolyte). In more concentrated solutions up the saturation for both electrolyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
219
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(229 citation statements)
references
References 48 publications
10
219
0
Order By: Relevance
“…In the previous studies, it was found that the following Hückel equations apply very well to the thermodynamic properties of NaCl [11], KCl [11], LiCl [19], RbCl [20], CsCl [20], and alkali metal bromide [21] solutions at least up to a molality of 1 mol Á kg À1 :…”
Section: Theorymentioning
confidence: 89%
See 3 more Smart Citations
“…In the previous studies, it was found that the following Hückel equations apply very well to the thermodynamic properties of NaCl [11], KCl [11], LiCl [19], RbCl [20], CsCl [20], and alkali metal bromide [21] solutions at least up to a molality of 1 mol Á kg À1 :…”
Section: Theorymentioning
confidence: 89%
“…In more concentrated solutions, the following extended Hückel equations were used here as earlier [11,[18][19][20][21] for the activity and osmotic coefficients:…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental data for γ exp ±,m at salt saturation are obtained from [91][92][93][94][95][96][97][98][99][100], and the values of K sp calculated from Equation (55) or taken from [101] are presented in Table 10. We predict the solubility limits at 298 K and 1.01 bar for a number of aqueous salt solutions using the solubility equation with the solubility product obtained from both Equations (42) and (55); the results are presented in Table 11 alongside the experimental solubility data [70,[102][103][104].…”
Section: Aqueous Solubility Of Saltsmentioning
confidence: 99%